Penerapan Metode Guided Writing Untuk Meningkatkan Keterampilan Menulis Deskripsi Sekolah Dasar Kelas Tinggi - Hana Nurlatifah; Din Azwar Uswatun; Arsyi Rizqia Amalia (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2020)
This study aims to describe the application and improvement of description writing skills through the guided writing method. The method of this research is Classroom Action Research (CAR) with a research design using the Kemmis and Mc Taggart models which were carried out in two cycles. Each cycle consists of planning actions, implementing actions, observing actions and reflecting actions. The subjects of this study were grade 5B students at SDI Al-Azhar 7 in Sukabumi City, 23 students, consisting of 11 male students and 12 female students. This research was conducted on April 29 to May 14, 2019. The technique of data collection was done by interviews, observation, tests, and documentation. The instrument of data collection is done by teacher and student observation sheets, interview sheets and description writing skills tests. Data analysis techniques were carried out in descriptive quantitative techniques. Observation results of teacher performance in cycles I and II experienced an increase of 18 points which obtained an average value of 66 and 84, while the results of observation of activities of students in cycles I and II experienced an increase of 18 points which obtained an average value of 64 and 82. Results Pre-cycle research writes a description of obtaining completeness of 34,78%. Then increasing in the first cycle reached completeness 47,83%. In the second cycle it continued to increase to reach completeness 82,61%. The conclusion of this study shows that the description writing skills of class 5B students increased through the application of guided writing methods.